Relations interethniques et métissages dans les aldeias indigènes de Rio de Janeiro : classifications ethniques et luttes politiques (XVIIIe et XIXe siècles) - Maria Regina Celestino de Almeida (Nuevo mundo - Mundos Nuevos, 2017)
During the Portuguese colonial period, numerous indigenous peoples were displaced from their lands and relocated to colonial villages (aldeias) on the outskirts of Rio de Janeiro. There the indigenous rebuilt their identities and, at the start of the nineteenth century, identified themselves – and were identified – as both Indians and mestizos. This article discusses the interethnic relations between Indians and non-Indians, focusing on the controversies over ethnic classifications, which are understood as political instruments. The documentation concerning land conflicts in the aldeias shows that alliances were established between Indians and non-Indians depending on the conflict. Ethnic classifications also varied accordingly; occasionally, some indigenous were considered to be non-Indians without losing their indigenous identity or classification. The rigid distinction between one and the other carried considerable political weight, which is clearly seen in the documentation. Without denying the conflicts of interest between Indians and colonists, especially those relative to land ownership, it is necessary to qualify them and deepen the profile of the actors involved.